Design and Implementation Factors for Performance Measurement in Non-profit Organizations: A Literature Review - Treinta, Fernanda T.; Moura, Louisi F.; Almeida Prado Cestari, José M.; Pinheiro de Lima, Edson; Deschamps, Fernando; Gouvea da Costa, Sergio Eduardo; Van Aken, Eileen M.; Munik, Juliano; Leite, Luciana R. (Frontiers in Psychology, 2020)
Purpose: Performance measurement systems (PMS) in Nonprofit Organizations (NPOs) are more complex than in for-profit organizations. NPOs have an orientation towards social mission and values, and they consider not only organizational efficiency and viability, but also the social impact of the organization. This research provides a comprehensive synthesis of PMSs in NPOs. Design/methodology/approach: Using a literature review, supported by bibliometric and network analyses. A paper set of 240 articles related to this research field is examined. Topics that are the most prevalent in this research area and their interrelationships are identified, presenting an outline of current efforts. Findings: Despite the descriptive analyses for the paper set, a framework is proposed for organizing the design-implementation factors of PMSs in nonprofit organizations, identifying the main requirements for their successful development. Originality/value: Investigation on performance measurement in nonprofit organizations is still in its early stages of development with many opportunities to further develop the field. Conceptual frameworks and models, as well as specific theories, are being generated for this field of research, and the process of adapting models from the general field of performance measurement is taking place. The meta-framework that organizes the main research topics of PMS in nonprofit organizations and the framework that consolidates factors that influence the design-implementation of PMSs in nonprofit organizations developed represents this paper contribution.